2017
DOI: 10.1038/s41598-017-09525-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia imaging in cells and tumor tissues using a highly selective fluorescent nitroreductase probe

Abstract: Hypoxia is a characteristic of locally advanced solid tumors, resulting from an imbalance between oxygen consumption and supply. In hypoxic solid tumors, an increased expression of nitroreductase (NTR) is detected, therefore, the development of NTR-targeted fluorescent probes to selectively and efficiently detect hypoxia in vivo is of utmost importance. In this study, a probe (1) has been designed and tested for effective optical detection of NTR in vitro and in vivo. The reduction of probe (1), catalyzed by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…S15 and S16). NTR is known existing in the cytoplasm of a mammalian cell (34,35). EM image of the NBC-Iod-CBT-treated hypoxic HeLa cells showed the existence of Iod-CBT-NPs with an average diameter of 53.3 ± 2.8 nm in the cytoplasm of the cells (Fig.…”
Section: Intracellular Formation Of Iod-cbt-npsmentioning
confidence: 95%
“…S15 and S16). NTR is known existing in the cytoplasm of a mammalian cell (34,35). EM image of the NBC-Iod-CBT-treated hypoxic HeLa cells showed the existence of Iod-CBT-NPs with an average diameter of 53.3 ± 2.8 nm in the cytoplasm of the cells (Fig.…”
Section: Intracellular Formation Of Iod-cbt-npsmentioning
confidence: 95%
“…Here, the new designed probe has a signicant difference in chemical structure, as shown in Scheme 1, to most of the reported probes, where the functional group was connected to the electron-donating end of the uorophore molecule. 9,16,19,23 Here, the azo group of the probe AZO-Cy connected to the electron-withdrawing end which is a rst report.…”
Section: Spectrum Of Probe Azo-cy Towards Cytochrome P450 Reductasementioning
confidence: 92%
“…[13][14][15] Because it is non-invasive, and has high sensitivity and high spatiotemporal resolution, uorescence imaging is still an ideal method for hypoxia detection. [16][17][18][19][20] As a metabolism enzyme, cytochrome P450 reductase plays a key role in the reduction of nitro functional compounds and has higher activity in cancerous cells than in normal cells, especially in a hypoxic environment. Several studies have proved that azo aromatic compounds are good substrates for cytochrome P450 reductase.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that findings from two-dimensional (2D, monolayer) cultured tumor cells differ from in vivo observations (Horman, 2016). Especially drug-induced regulation of HIF-1a observed in cell culture experiments has to be considered critical as solid tumors are often exposed to hypoxia and thus already feature HIF-1a overexpression (Zhong et al, 1999;Yang et al, 2017). To assess the biologic relevance of in vitro data, testing drug effects in 3D-cultured cells is state-of-the-art in cancer research, because 3D-cultured cells have similar characteristics as in vivo and are considered in vitro microtumor models (Ivascu and Kubbies, 2006).…”
Section: Hif-1a Regulation By Opioids In Breast Cancer Cellsmentioning
confidence: 99%